Emotional Experiences and Regulation in the Workplace: The Effects of Culture - Ibrahim, Habibie; Johnson, Sally; Gilligan, Philip (UUM Press, 2016)
The present research aimed to investigate the experienced emotions and emotional regulation in the workplace particularly in child and family social work practice in a Malaysian context. The interrelationship between emotion and emotional regulation and cultural context were explored. The overall research strategy was ethnographic. The researchers used a mixture of methods including individual interviews, participant observation, and a questionnaire. The research was conducted in three locations in Malaysia: Kuala Lumpur, Petaling and Kota Kinabalu. Participants consisted of child protectors and rehabilitation officers from the Malaysia Welfare Department and medical social workers in hospitals. This paper presents an analysis of individual interviews in the three locations. A total of twenty-five interviews were conducted (12 male, 13 female; age range 29-51). Data were analysed using thematic analysis . The research findings show that societal and professional cultures have influenced how child social workers regulate their experienced emotion when dealing with clients.